Chronic constrictive pericarditis: an “Egg-Shell” calcification - Patel, Ramesh; Gohel, Rohit (International Journal of Research in Medical Sciences, 2019)
Chronic constrictive pericarditis is a condition marked by scarred and inelastic pericardium with excessive fibrous tissue and calcium. Here, we report a case of Egg-Shell like calcification in a 30-year-old young adult diagnosed with chronic constrictive pericarditis. The patient was successfully managed with very good prognosis post-pericardiectomy.